O rural agrícola na metrópole: o caso de Porto Alegre/RS - Éverton de Moraes Kozenieski; Rosa Maria Vieira Medeiros (Confins)
Rural spaces have shown significant changes in recent decades in Brazil. In them are new characteristics among which we can highlight the extinction of spaces for agricultural practices due to the urban expansion and reconfiguration of uses in rural areas resulting from new functions and economic activities. The municipality of Porto Alegre (Brazil), which had an intense urban expansion, was the scene of major changes in its territory with significant loss of its rural characteristics, which even put it in the metropolis condition among the Brazilian urban network. Considering this context characterized by the presence of conflicts caused by urban expansion and the consequent termination of agricultural practices, this article aims to analyze the main economic, political and cultural elements that contribute to maintaining spaces for agriculture in large urban centers using the local farmers vision from the municipality of Porto Alegre / RS.